Delving into quasi-periodic type optical solitons in fully nonlinear complex structured perturbed Gerdjikov–Ivanov equation - Yan, Zhimin; Li, Jinbo; Barak, Shoaib; Haque, Salma; Mlaiki, Nabil (Scientific reports, 2025)
In this study, we aim to explore the soliton phenomena in fully nonlinear complex perturbed Gerdjikov–Ivanov equation (PGIE). This model concerns with optical pulse transmission pursuant to perturbation impacts encompassing significant uses in optical fibers, especially, photonic crystal fibers. We employ the Riccati modified extended simple equation method, which has never been employed for this model previously, to acquire novel and distinct optical soliton solutions. To visually evaluate the dynamics of derived optical soliton solutions, several 3D, 2D, and contour graphics are incorporated. These visuals reveal a range of quasi-periodic type optical soliton phenomena, that include internal envelope, hump, cnoidal, periodic, and fractal solitons. In addition to including additional soliton dynamics into the model, the results show how these dynamics interact to affect the system’s overall behavior.